2016
DOI: 10.1080/19401493.2016.1243731
|View full text |Cite
|
Sign up to set email alerts
|

International survey on current occupant modelling approaches in building performance simulation

Abstract: It is not evident that practitioners have kept pace with latest research developments in building occupant behaviour modelling; nor are the attitudes of practitioners regarding occupant behaviour modelling well understood. In order to guide research and development efforts, researchers, policy-makers, and software developers require a better understanding of current practice and acceptance of occupant modelling. This paper provides results, analysis, and discussion of the results of a 36-question international… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 36 publications
(41 reference statements)
0
27
0
1
Order By: Relevance
“…1a. Publisher Purpose DOE (1979) [9] Development of Building Energy Performance Standards (BEPS) legislation ASHRAE (1989) [10] Building Energy Cost Budget (ECB) Method: Code compliance via simulation ASHRAE (2004) [11] Building Performance Rating Method: Estimation of % energy savings of advanced building designs DOE/NREL (2011) [12] DOE commercial building research: technology assessment, design optimization, analyze advanced controls, develop energy codes and standards, and to conduct lighting, daylighting, ventilation, and indoor air quality studies ASHRAE (2013) [13,14] Envelope trade-off: Envelope code compliance via simulation On the building-scale, standard schedules are widely used for code compliance, systems design, and research purposes as intended by their publishers [12,21,22].…”
Section: Origins and Purposes Of Standard Occupancy Schedulesmentioning
confidence: 99%
“…1a. Publisher Purpose DOE (1979) [9] Development of Building Energy Performance Standards (BEPS) legislation ASHRAE (1989) [10] Building Energy Cost Budget (ECB) Method: Code compliance via simulation ASHRAE (2004) [11] Building Performance Rating Method: Estimation of % energy savings of advanced building designs DOE/NREL (2011) [12] DOE commercial building research: technology assessment, design optimization, analyze advanced controls, develop energy codes and standards, and to conduct lighting, daylighting, ventilation, and indoor air quality studies ASHRAE (2013) [13,14] Envelope trade-off: Envelope code compliance via simulation On the building-scale, standard schedules are widely used for code compliance, systems design, and research purposes as intended by their publishers [12,21,22].…”
Section: Origins and Purposes Of Standard Occupancy Schedulesmentioning
confidence: 99%
“…Based on this literature review, a number of shortcomings of the existing models may be revealed. First, models in literature do not account sufficiently to household variables while quantifying residential energy consumption [49]. In most of the approaches, the only variable considered for representing households' attributes is the number of occupants (e.g.…”
Section: Research Gaps With Regard To Occupant-related Energy Consumpmentioning
confidence: 99%
“…Moreover, the framework allows assessing energy consumption variability between different household profiles. Given these features, such a model may thus be coupled to industrial energy simulators to produce more accurate energy estimations with a reduced uncertainty [49]. This is a substantial point for addressing the growing market of 'energy performance contracts'.…”
mentioning
confidence: 99%
“…A survey on occupant modeling approaches in building simulations [5] showed that 66% of the researchers modeled the thermostat set point as a daily schedule, while another 16% used a constant for the entire year. Very few researchers have explicitly acknowledged the occupants' interaction with the thermostats.…”
Section: Introductionmentioning
confidence: 99%